Hadis “Man Baddala Dînahû Faqtulûhu”: Telaah Semiotika Komunikasi Hadis - Benny Afwadzi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
This article attempts to understand the hadith Man baddala dînahû faqtulûhu, with the communication semiotics of hadith adopted from the theory of communication semiotics of Umberto Eco. to this study, I conclude that the Prophet as delivered sources of the tradition toward our semiotic mind as the destination through some communication components. After the processing of  unlimited semiosis in the destination, the appeared understanding fabric related to the word faqtulûhu in the tradition refer to the meaning “warn him”, and then it could be saying “give him advice.” And further reinterpretation to be “honor him. “The latter Interpretant could be the final logical interpretant that has a great contribution to the modern context.[Artikel ini mencoba untuk memahami hadits Man baddala dînahû faqtulûhu, dengan menggunakan pembacaan semiotika komunikasi hadits yang diadopsi dari teori semiotika komunikasi Umberto Eco. Dalam penelitian ini, saya menyimpulkan bahwa Nabi sebagai sumber penyampai hadis pertama disampaikan melalui alam pikiran semiotik kita melalui beberapa komponen komunikasi. Setelah melalui proses semiosis yang tak terbatas di dalam tujuan komunikasi itu, ada pemahaman muncul terkait dengan kata “faqtulûhu” dalam hadis merujuk pada makna “memperingatkan dia”, dan bisa juga bermakna “memberikan nasihat kepadanya.” Adapun penafsiran selanjutnya menjadi “menghormati dia.” Tafsiran yang terakhir dianggap cukup masuk akal dan banyak memberikan kontribusi besar bagi kehidupan konteks modern.]